The Next Instalment : Serials, Sequels, and Adaptations of Nellie L. McClung, L.M. Montgomery, and Mazo de la Roche - Roy, Wendy, 1957- (Book collections on Project MUSE., 2019)
"It's about three Canadian writers and how, under the influence of publishing practices of early-20th- century Canada, they became practitioners of the continuing story (i.e., stories that appeared in instalments)."--